PENYULUHAN PARENTING DIGITAL ISLAMI UNTUK MENINGKATKAN LITERASI PENGASUHAN WALI MURID ANAK USIA DINI TK ABA GANTIWARNO LAMPUNG TIMUR - Samson Fajar; Muhammad Nur (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The rapid growth of digital technology has significantly transformed early childhood parenting practices, particularly among families with limited digital literacy. Many parents rely on gadgets as behavioral management tools without adequate guidance, potentially affecting children’s social, emotional, and moral development. This community service program aimed to enhance digital parenting literacy among parents of TK ABA 2 Gantiwarno, Lampung Timur, by promoting wise and value-based technology use. The program employed interactive counseling sessions, participatory discussions, simple case studies, and reflective exercises grounded in Islamic parenting principles. The results indicate improved parental awareness of screen time management, active mediation, and the importance of role modeling in digital behavior. Participants demonstrated stronger commitment to responsible digital supervision and collaborative engagement with the school. This initiative highlights the strategic role of community-based parenting education in strengthening families as the primary foundation for character development in the digital era.